Tingkat Risiko Kawasan Rawan Banjir di Kecamatan Komodo Kabupaten Manggarai Barat - Olandina De Rosari Lede; Moch. Shofwan (Prosiding, 2023)
Komodo District is also one of the areas that is prone to disasters, especially floods, as happened in 2019 when a flood hit three villages, namely Gorontalo Village, Macang Tanggar Village and Golo Bilas Village, Komodo District. The purpose of this study was to determine the risk level of flood-prone areas in Komodo District, West Manggarai Regency. Methods of data collection in this study using documentation, observation, literature studies and related institutions. The analytical method used is quantitative descriptive analysis with overlay analysis techniques. The results showed that based on the results of the risk assessment analysis for West Manggarai Regency, the index for the flood hazard class for Komodo District was the moderate class index. This is in line with the results of research conducted where the Komodo District is included in the moderate risk level.